Proceedings of the 1999 ACM SIGMETRICS International Conference on Measurement and Modeling of Computer Systems 1999
DOI: 10.1145/301453.301580
|View full text |Cite
|
Sign up to set email alerts
|

Supporting best-effort traffic with fair service curve

Abstract: While PFQ algorithms can provide per-flow end-to-end delay guarantees for real-time traffic or protection among competing best-effort traffic, they have two important limitations. The first one is that, since only one parameter (a weight) is used to allocate resource for each flow, there is a coupling between delay and bandwidth allocation. When used for real-time traffic, this can result in network under-utilization. The second and less well known limitation is that, when used for best-effort traffic, PFQ alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In this paper, we present only a subset of our simulation results. Additional simulation results are presented in [14].…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we present only a subset of our simulation results. Additional simulation results are presented in [14].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…To compute the timestamps, we need to remember what part of the service curve was used to compute the timestamp of the previous packet. The details of the virtual time computation and algorithm pseudocode can be found in [14].…”
Section: Fair Service Curve Algorithmmentioning
confidence: 99%
“…As discussed below, the primary goal of these algorithms is to divide up the bandwidth in a specified manner between the flows; they do not explicitly attempt to control the latencies of the requests. The second class of scheduling algorithms based on survice curves [7,19,23,26] attempt to simultaneously control both the bandwidth allocation and the latencies of the flows. Finally, storage-specific methods such as Façade [17], Stonehenge [13], SFQ(D) [15] and Avatar [28], either use variants of virtual-time based tagging or a feedback based mechanism to provide heuristic assurances.…”
Section: Related Workmentioning
confidence: 99%
“…Stoica et al [19,26] have identified cases where SCED may fail and have provided a modified virtual-time based algorithm to avoid starving a client for using excess capacity. However they don't guarantee that the client can meet its deadline if it uses the excess capacity.…”
Section: Algorithms Based On Service Curvesmentioning
confidence: 99%
“…Other forms of QoS control that take account of flow duration have been proposed as related work [11], [12]. However, they require that each node has a mechanism for per-flow scheduling or per-flow accounting.…”
Section: Introductionmentioning
confidence: 99%